Reliability and validity of neurobehavioral function on the Psychology Experimental Building Language test battery in young adults - Piper, Brian J.; Mueller, Shane T.; Geerken, Alexander R.; Dixon, Kyle L.; Kroliczak, Gregory; Olsen, Reid H.J.; Miller, Jeremy K. (PeerJ, 2015)
Background. The Psychology Experiment Building Language (PEBL) software consists of over one-hundred computerized tests based on classic and novel cognitive neuropsychology and behavioral neurology measures. Although the PEBL tests are becoming more widely utilized, there is currently very limited information about the psychometric properties of these measures. Methods. Study I examined inter-relationships among nine PEBL tests including indices of motor-function (Pursuit Rotor and Dexterity), attention (Test of Attentional Vigilance and Time-Wall), working memory (Digit Span Forward), and executive-function (PEBL Trail Making Test, Berg/Wisconsin Card Sorting Test, Iowa Gambling Test, and Mental Rotation) in a normative sample (N = 189, ages 18–22). Study II evaluated test–retest reliability with a two-week interest interval between administrations in a separate sample (N = 79, ages 18–22). Results. Moderate intra-test, but low inter-test, correlations were observed and ceiling/floor effects were uncommon. Sex differences were identified on the Pursuit Rotor (Cohen’s d = 0.89) and Mental Rotation (d = 0.31) tests. The correlation between the test and retest was high for tests of motor learning (Pursuit Rotor time on target r = .86) and attention (Test of Attentional Vigilance response time r = .79), intermediate for memory (digit span r = .63) but lower for the executive function indices (Wisconsin/Berg Card Sorting Test perseverative errors = .45, Tower of London moves = .15). Significant practice effects were identified on several indices of executive function. Conclusions. These results are broadly supportive of the reliability and validity of individual PEBL tests in this sample. These findings indicate that the freely downloadable, open-source PEBL battery (http://pebl.sourceforge.net) is a versatile research tool to study individual differences in neurocognitive performance.
Keywords: Attention; Executive function; Learning; Motor; Memory; Cognition; Neuropsychology; Decision making; Sex differences; Human